1984
DOI: 10.1017/s0022112084000847
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase displacement in Hele-Shaw cells: experiments on viscously driven instabilities

Abstract: Experiments on the instability of the interface in two-phase displacements in Hele-Shaw cells were conducted using air and a viscous oil as the working fluids. The experiments had two objectives: (i) to provide quantitative measurements of the growth constants of the instability which occurs when a less-viscous fluid displaces a more-viscous one, and (ii) to compare the measured dispersion relations with the predictions of the recent theory of Park & Homsy (1984). The experiments were made by analysing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 5 publications
5
22
2
Order By: Relevance
“…For small values of Ca, perform asymptotic expansions in order to determine the dominant wavelength. Their results, which were confirmed by the experiments of Park, Gorell & Homsy (1984), yield much larger wavelengths than found here. Subsequently, Maxworthy (1989) compiled experimental results by several authors for the dominant wavelength over a range of Ca (10 −3 < Ca < 30).…”
Section: Comparison With Results Obtained From Darcy's Lawsupporting
confidence: 90%
“…For small values of Ca, perform asymptotic expansions in order to determine the dominant wavelength. Their results, which were confirmed by the experiments of Park, Gorell & Homsy (1984), yield much larger wavelengths than found here. Subsequently, Maxworthy (1989) compiled experimental results by several authors for the dominant wavelength over a range of Ca (10 −3 < Ca < 30).…”
Section: Comparison With Results Obtained From Darcy's Lawsupporting
confidence: 90%
“…This indicates that the capillary pressure is controlled by the interface curvature in the plane of the fracture. This result was already noticed in numerous studies of immiscible fluids displacement in a Hele Shaw cell (Bensimon et al 1986;Park et al 1984;Zhang et al 1998). We have seen, in the aperture field measurement section, that the correlation length of the aperture is of the same order of magnitude as the mean aperture.…”
Section: Finger Widthsupporting
confidence: 81%
“…This allows defining the conditions required to get fingering and to investigate the length scale of the fingers. A slight modification of the calculation of the capillary pressure was performed (Park et al 1984), giving a better agreement with the width of the fingers. Recent studies have shown that a quantitative analysis of fingering in a heterogeneous fracture is confronted to an indetermination of the capillary pressure.…”
mentioning
confidence: 99%
“…Since Hill (1952) reported his pioneering observation on viscous fingering phenomenon, this issue has been intensively studied by many researchers both experimentally and theoretically. As for experimental researches, the Hele-Shaw cell, which is composed of two closely spaced parallel plates, is often employed to investigate the similar fluid state in porous media due to the mathematical analogy of motions in both situations (Park et al 1984;Moore et al 2002;Toussaint et al 2005). Although Homsy pointed out that the analogy fails completely in the case of immiscible displacement because the forces associated with the propagation of the menisci through the pore space are not considered in Hele-Shaw geometry, the Hele-Shaw cell is of fundamental interest and still helpful for developing useful concepts (Zimmerman and Homsy 1991).…”
mentioning
confidence: 99%